Pemanfaatan Learning Management System (LMS) Muga E-Learning Pada Mata Pelajaran Ekonomi di SMA - Vionita, Deviyani; Handayani, Trisni (Jurnal Ilmiah Global Education, 2025)
Amid the rapid development of the digital era, technology has played a vital role in various aspects of life, including the education sector. This study aims to describe the utilization of a Learning Management System (LMS) and the implementation of several digital learning features namely e-modules, quizzes, and assessments in the teaching and learning process of economics in grade X of senior high school. The research employed a descriptive qualitative method, with observation, interviews, and documentation as data sources. The results of the study indicate that the e-module, quiz, and assessment features in the LMS can enhance student engagement, trengthen understanding of the material, and facilitate teachers in monitoring learning outcomes in real time. These three elements complement each other in creating effective, efficient, and adaptive economics learning aligned with advancements in educational tech .  It is recommended that future LMS development includes increased file upload capacity, optimized loading for large content files, and the provision of offlline access features to overcome network limitations.